ANALISIS PERBAIKAN PROSES PRODUKSI TAHU PADA UKM TAHU BERKAH BAROKAH - Sagita, Dandi; Fajrah, Nofriani (Computer Science and Industrial Engineering, 2025)
This study aims to analyze and propose improvements to the tofu production process at UKM Tahu Berkah Barokah based on Good Manufacturing Practice (GMP) and Workplace Improvement Strategies and Ergonomics (WISE) standards. Observations revealed several critical non-conformities, including an unclean and poorly maintained factory environment, inadequate sanitation facilities, and low employee awareness of personal hygiene. The average defect rate reached 14.98% per month, or 21,750 pieces out of 145,050 total production. The calculated DPMO value of 37,480 with a sigma level of 3.28 indicates inefficiencies in the process, while the Cpk value of 1.00 falls below the industry standard (≥1.33). Proposed improvements include enhancing workplace cleanliness, providing sanitation and OHS training, implementing production process supervision through documentation and regular audits, and encouraging active employee involvement in workplace innovation. The integration of GMP and WISE approaches is expected to reduce production defects, improve product quality, and create a healthier and more productive working environment on a sustainable basis.